Where's the disagreement? The significance of the ordinary in Austin and Ayer. (July 2016) - Forsberg, Niklas
Abstract: J. L. Austin is commonly known as an 'ordinary language philosopher'. Ordinary language philosophy, in turn, is generally known as a philosophy of language which employs everyday language as a standard of correctness – an arbiter between meaningful speech and nonsense. By means of a return to the somewhat heated debate between Austin and A. J. Ayer, this paper challenges this picture. I argue that if there is one philosophical tradition that encourages us to turn 'ordinary language' into a problem for philosophy, it is ordinary language philosophy. There is no simple instruction of the form 'If you are philosophically troubled, then turn to ordinary language and you will see the true sense' coming out of Austin's work (rightly construed). Highlights: If there is one philosophical tradition that encourages us to turn 'ordinary language' into a problem for philosophy, it is ordinary language philosophy. Ordinary language is not a standard of correctness. Ordinary language philosophy should never have become a 'philosophy of language'.